D-Mannose Regulates Hepatocyte Lipid Metabolism via PI3K/Akt/mTOR Signaling Pathway and Ameliorates Hepatic Steatosis in Alcoholic Liver Disease - Hu, Mengyao; Chen, Yu; Deng, Fan; Chang, Bo; Luo, Jialiang; Dong, Lijun; Lu, Xiao; Zhang, Yi; Chen, Zhengliang; Zhou, Jia (Frontiers in Immunology, 2022)
This study investigated the protective properties and mechanisms of D-mannose against hepatic steatosis in experimental alcoholic liver disease (ALD). Drinking-water supplementation of D-mannose significantly attenuated hepatic steatosis in a standard mouse ALD model established by chronic-binge ethanol feeding, especially hepatocyte lipid deposition. This function of D-mannose on lipid accumulation in hepatocytes was also confirmed using ethanol-treated primary mouse hepatocytes (PMHs) with a D-mannose supplement. Meanwhile, D-mannose regulated lipid metabolism by rescuing ethanol-mediated reduction of fatty acid oxidation genes (PPARα, ACOX1, CPT1) and elevation of lipogenic genes (SREBP1c, ACC1, FASN). PI3K/Akt/mTOR signaling pathway was involved in this effect of D-mannose on lipid metabolism since PI3K/Akt/mTOR pathway inhibitors or agonists could abolish this effect in PMHs. Overall, our findings suggest that D-mannose exhibits its anti-steatosis effect in ALD by regulating hepatocyte lipid metabolism via PI3K/Akt/mTOR signaling pathway.